EFEKTIVITAS PROGRAM ADOLESCENCE CHARACTER BUILDING (ACB) TERHADAP PENANAMAN KARAKTER REMAJA DI KABUPATEN SUMBAWA - Erliana, Yossy Dwi; Hartono, Roni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Adolescence is an important stage in human development. This study aims to determine the effectiveness of the Adolescence Character Building (ACB) program in order to build of adolescents characters in Sumbawa Regency. The population is high school students in the capital of Sumbawa Regency by using samples of students of SMAN 2 Sumbawa Besar. The program was conducted for three days on July 16th, 18th and 19th.  The independent variable is ACB program, while the dependent variable is character understanding in adolescent. The participants are given a pre-test sheet. Program was delivered by instruction (lecture), discussion, simulation, and game. During learning the particiants get eight ACB modules, namely (1) Introduction of Self; (2) Learning Styles; (3) Goal, Mission, and Time Management; (4) Reactive and Proactive; (5) Conflict Management; (6) Assertive and Critical Thinking; (7) Empathy and Respect for Others; and (8) Leadership. After the program is completed the participants are given post-test sheet. The effectiveness of the program was analyzed using the Wilcoxon Signed-Ranks test to examine differences student’s understanding about the value of character between before and after program intervention. The results of this study indicate that there is influence of ACB program implementation on the participants. The post-test score is higher than the pre-test score. The effectiveness of the program during the study may be due to internal and external factors. Internal factors such as an understanding of some participants to the values ​​of character. External factors include an appropriate and fun methods, relevant material and professional instructor.